Perceptions of Artificial Insemination Among Members of the Christ Apostolic Church, Oke-Ife DCC Headquarters, Ibadan: A Religio-Ethical Analysis - Oyebanji, Israel Temitope (MAHABBAH: Journal of Religion and Education, 2024)
This study investigates the perceptions of artificial insemination (AI) among members of the Christ Apostolic Church (CAC), Oke-Ife District Coordinating Council (DCC) Headquarters in Ibadan, Nigeria. Utilising a mixed-methods approach, data were collected through structured questionnaires and semi-structured interviews from 475 respondents. The findings reveal a nuanced and often divided perception toward AI, with 58.94% of respondents affirming that AI is not inherently sinful, and 69.32% recognising it as a medical breakthrough. However, 52.91% associate AI with a lack of faith in divine intervention, indicating a deep theological tension between medical science and spiritual reliance. The research identifies biblical interpretation, doctrinal teachings, gender roles, and cultural expectations as key determinants of perception. Ethical concerns such as marital fidelity, procreation, spiritual integrity, donor anonymity, and lineage identity are central to the discourse. The study further explores alternative solutions to infertility, including adoption, fostering, and spiritual child-naming, which are increasingly being considered within the Christian community. It concludes that while medical advancements are acknowledged, theological convictions significantly shape the acceptance or rejection of AI. The research recommends enhanced theological education on bioethical issues, development of pastoral counselling frameworks, and inclusive dialogue within Christian communities to address infertility with both compassion and doctrinal clarity. This work contributes to the intersection of theology, ethics, and reproductive technologies in African Christian contexts.